Reflection of Faith in Dan Brown's The Da Vinci Code Novel (2003): New Criticism - Tridiarto, Agitya Agung; Nurhidayat, Nurhidayat (English Department, Faculty of Humanities, Andalas University, 2023)
The Da Vinci Code Novel is one of the famous works from Dan Brown, it narrates about the conflict between Priory of Sion and the church a long time ago. The novel would show us the sacred of Holy Grail which has been covered and the mystery of the codes. The conflict of faith is something that makes the novel complicated and more interesting to read. a faith is also important in determining people’s life because it is an attitude even though it is not always true, thus it cannot become a standard of truth. The writer uses New Criticism approach to find the main problem and conflicts related to research question. The writer also uses a qualitative method to describe the finding. In the end of the study, the writer finds that The Da Vinci Code novel have several faiths reflected, namely; (1) the last supper painting that breaks people’s faith, (2) holy grail and the secret of Christianity’s faith, (3) the priory of sion as the guardian, and (4) the truth of faith. At the same time, the main problem in the novel is a different perspective on the Holy Grail due to the lack of relevant information and their long-established faith, thus they assume that it is true. We cannot claim either of them was wrong because it refers to their own needs. In fact, there is no absolute truth for human being, it is because the truth we have is only own perspective and it does not apply for everyone.